IMPLEMENTASI BAURAN KOMUNIKASI PEMASARAN DALAM MENINGKATKAN PENJUALAN DI UD. MEKAR CHANDRA JAYA MAJENANG - Lestari, Diana Muji; Wafi, Inngamul; Solihun (STKIP MAJENANG, 2023)
The rapid development of the automotive industry in Indonesia has made the level of competition even tighter, especially in the motorcycle industry. This needs to be done so that companies can work for other people to be able to compete in the free market. Therefore, companies compete in promotional media. UD. Mekar Chandra Jaya Majenang is one of the official HONDA dealers in collaboration with the FIF Group leasing company. UD. Mekar Chandra Jaya Majenang requires communication between companies and consumers that can be used to introduce products or services by using and implementing a marketing communication mix. The purpose of implementing the marketing communication mix is to select and implement which sales promotion channels are appropriate to increase sales and obtain reciprocal communications from consumers to obtain positive publicity among the public. The company also continues to improve and innovate on sales strategies to increase product sales volume.